Risperidone Induced Hyperprolactinemia: From Basic to Clinical Studies - Stojkovic, Milena; Radmanovic, Branimir; Jovanovic, Mirjana; Janjic, Vladimir; Muric, Nemanja; Ristic, Dragana Ignjatovic (Frontiers in Psychiatry, 2022)
Risperidone is one of the most commonly used antipsychotics(AP), due to its safety and efficacy in reducing psychotic symptoms. Despite the favorable side effect profile, the therapy is accompanied by side effects due to the non-selectivity of this medicine. This review will briefly highlight the most important basic and clinical findings in this area, consider the clinical effects of AP-induced hyperprolactinemia (HPL), and suggest different approaches to the treatment.The route of application of this drug primarily affects the daily variation and the total concentration of drug levels in the blood, which consequently affects the appearance of side effects, either worsening or even reducing them. Our attention has been drawn to HPL, a frequent but neglected adverse effect observed in cases treated with Risperidone and its secondary manifestations. An increase in prolactin levels above the reference values result in impairment of other somatic functions (lactation, irregular menses, fertility) as well as a significant reduction in quality of life. It has been frequently shown that the side effects of the Risperidone are the most common cause of non-compliance with therapy, resulting in worsening of psychiatric symptoms and hospitalization.However, the mechanism of Risperidone-induced HPL is complicated and still far from fully understood. Most of the preclinical and clinical studies described in this study show that hyperprolactinemia is one of the most common if not the leading side effect of Risperidone therefore to improve the quality of life of these patients, clinicians must recognize and treat HPL associated with the use of these drugs.